2011
DOI: 10.1007/s10389-011-0448-9
|View full text |Cite
|
Sign up to set email alerts
|

The attitude of farmers to the New Rural Cooperative Medical Scheme in Northwest China one year after its introduction: a cross-sectional study

Abstract: Aim The implementation of the Chinese New Rural Cooperative Medical Scheme (NRCMS) spread fast since a county pilot trial in 2003. The purpose of this survey is to guide policy-makers on how to improve the current national NRCMS policy. Subject and methods Cross-sectional survey of 1,978 farmers in 50 villages in Huxian Shaanxi Province on their attitudes towards the NRCMS administered door-to-door in 2005.Results Most farmers hold a positive attitude towards the NRCMS. However, they do not trust the scheme ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…And as for the ampli cation, in urban hospital, master degree gets the rst place and bachelor degree comes the second, while in township hospitals, bachelor degree is the largest and the following is college degree. Then, seen from the professional title in 2015, the proportion of the advanced and intermediate title in urban hospital is 56.5% altogether, compared with 24.7% in township hospital [25,26].…”
Section: Education Attainment and Professional Titlementioning
confidence: 99%
See 1 more Smart Citation
“…And as for the ampli cation, in urban hospital, master degree gets the rst place and bachelor degree comes the second, while in township hospitals, bachelor degree is the largest and the following is college degree. Then, seen from the professional title in 2015, the proportion of the advanced and intermediate title in urban hospital is 56.5% altogether, compared with 24.7% in township hospital [25,26].…”
Section: Education Attainment and Professional Titlementioning
confidence: 99%
“…A survey studying the reasons why people prefer urban hospitals showed that (multiple choices are permitted): good technology(29%), good service attitude(51%), good facilities (26%) [25,26]. Therefore, no matter for patients and doctors, the better condition of urban hospitals is a main attraction.…”
Section: Education Attainment and Professional Titlementioning
confidence: 99%
“…It is a voluntary program and the voluntary feature was adopted to overcome public mistrust in the government-run insurance program ( 8 , 9 ). The survey showed a high enrolment rate of 92% in this voluntary insurance scheme ( 10 ). Based on fee-for-service and cost-sharing models, the NRCMS mainly applies to inpatient services and some medical outpatient services, aiming to reduce the burden of disease costs for the rural population ( 8 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, the Chinese government launched the New Rural Cooperative Medical Scheme (NRCMS), a government-run system that differed from the previous one in two aspects: (i) farmers contributed to a county-level rather than a town-level financing pool [ 13 ]; and (ii) participation was voluntary rather than mandatory. One of the main goals of the system is to address catastrophic medical payments [ 14 ].…”
Section: Introductionmentioning
confidence: 99%